Textile Composites and Inflatable Structures II - Oñate, Eugenio; Kröplin, Bernd; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2008)
Textile composites and inflatable structures have become increasingly popular for a variety of applications in – among many other fields – civil engineering, architecture and aerospace engineering. Typical examples include membrane roofs and covers, sails, inflatable buildings and pavilions, airships, inflatable furniture, airspace structures etc. The ability to provide numerical simulations for increasingly complex membrane and inflatable structures is advancing rapidly due to both remarkable strides in computer hardware development and the improved maturity of computational procedures for nonlinear structural systems. Significant progress has been made in the formulation of finite elements methods for static and dynamic problems, complex constitutive material behaviour, coupled aero-elastic analysis etc. The book contains 14 invited contributions written by distinguished authors who participated in the Second International Conference on Textile Composites and Inflated Structures held in Stuttgart, 2-4 October 2005. The meeting was one of the Thematic Conferences of the European Community on Computational Methods in Applied Sciences (ECCOMAS, www.eccomas.org ). The different chapters discuss recent progress and future research directions in new textile composites for applications in membrane and inflatable structures. Part of the book focuses in describing innovative numerical methods for structural analysis, such as new non linear membrane and shell finite elements. The rest of the chapters present advances in design, construction and maintenance procedures. This volume contains state-of-the-art research and technology for design, analysis, construction and maintenance of textile and inflatable structures and will be of interest to civil engineers, architects, and materials scientists.
Innovative Developments in Fiber Based Materials for Construction -- Finite Element Simulation of the Mechanical Behaviour of Textile Composites at the Mesoscopic Scale of Individual Fibers -- A Predictive Fabric Model for Membrane Structure Design -- Modelling Fabric-Reinforced Membranes with the Discrete Element Method -- Introducing Cutting Patterns in Form Finding and Structural Analysis -- Kinematics in Tensioned Structures -- Pneumatic Formwork for Irregular Curved Thin Shells -- Static Analysis of Taut Structures -- Analysis of Free Form Membranes Subject to Wind Using FSI -- Membrane Structures Formed by Low Pressure Inflatable Tubes. New Analysis Methods and Recent Constructions -- Nonlinear Finite Element Analysis of Inflatable Prefolded Membrane Structures under Hydrostatic Loading -- Advanced Capabilities for the Simulation of Membrane and Inflatable Space Structures Using SAMCEF -- Structural Air — Pneumatic Structures -- Recent Developments in the Computational Modelling of Textile Membranes and Inflatable Structures.
Keywords: Materials science; Mechanics; Mechanics, Applied; Buildings—Design and construction; Building; Construction; Engineering, Architectural; Materials Science, general; Solid Mechanics; Building Construction and Design